Unveiling The Burden of Bone Mineral Density in Chronic Kidney Disease Patients on Hemodialysis: Insights into Risk Factors - Mahajan, Kishalay; Tripathi, Pratik; Khandelwal, Gaurav; Mehta, Shaurya; Baidya, Ankur (National Journal of Medical Research, 2025)
Background: Chronic Kidney Disease (CKD) is a growing global health burden, often complicated by mineral and bone disorders (CKD-MBD) that significantly increase fracture risk. This study aims to establish the proportion of CKD-MBD among hemodialysis patient and to establish correlation between intact PTH (iPTH) and bone mineral density in dialysis patients. Methods: A cross-sectional study was conducted at the National Institute of Medical Sciences, Jaipur, involving 100 adult CKD patients on maintenance hemodialysis between August 2024 and January 2025. BMD was assessed using Dual-Energy X-ray Absorptiometry (DEXA) at the lumbar spine and femoral neck. Clinical, anthropometric, and laboratory data including intact parathyroid hormone (iPTH), alkaline phosphatase (ALP), vitamin D, and hemoglobin were collected. Fracture risk was analyzed using Pearson correlation and multivariate logistic regression. Results: Among the 100 patients, mean age was 44.6 ± 14.1 years. The multivariate logistic regression analysis identified age >45 years, presence of diabetes, and moderate iPTH levels as significant independent predictors of high fracture risk in chronic kidney disease (CKD) patients. Serum albumin positively correlated with BMD at the radius-ulna site. Conclusion: This study highlights elevated iPTH and ALP levels, older age, and diabetes as key predictors of low BMD and high fracture risk in CKD patients on hemodialysis. Routine BMD assessment and monitoring of CKD-MBD parameters are essential for timely intervention. These findings emphasize the need for integrated bone health management strategies in this CKD on hemodialysis patients.